Mechanical Behaviour of Irvingin Malayana Nut Under Compressive Loading - Chusilp, Somnuk; Sudajan, Somposh (Engineering and Applied Science Research, 2013)
Smooth-shell lowland and upland varieties of Irvingia Malayana nut were subjected to compressive loading along two major planes at four loading speeds to determine the force application and investigate the behavior of the nut in relation to the design and development of nut shelling machine. Test results are concluded as follows: The maximum compressive forces required to crack nuts axially and laterally were 1,499 N and 2,912 N for the lowland variety. The mean compressive force for axial compression was lower than lateral compressive force for axial compression was than lateral compression with a saving in load of 32%. The maximum compressive forces required to crack nuts axially and laterally were 1,421 N and 1,868 N for the upland variety. The mean compressive forces for axial compression was higher than lateral than lateral compression, and both were significantly different in the range of 0.83 to 2.92 mm/s loading speeds. The deformation values of shelled rupture were between 1.5-3.5 mm. for lowland variety and 1.0 – 2.0 mm. for upland variety. The shelling of nut at the tip position by using an axial compression is recommended.